2006
DOI: 10.1177/0145445504264750
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Structured Descriptive Assessment With Typically Developing Children

Abstract: To date, only a limited number of studies have focused on functional assessment with typically developing populations. The most commonly reported method of functional assessment with this population seems to be descriptive assessment; however, the methods used in the descriptive assessment often are unclear. This is unfortunate as researchers and practitioners often are left with little guidance as to how to conduct a functional assessment with typically developing children. The purpose of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The method of the structured descriptive assessment used in this study generally replicates that used and pioneered by Anderson and colleagues (Anderson & Long, 2002;Anderson et al, 2006;Freeman et al, 2000). However, this study differs from those listed in respect of the data analysis techniques used, which are more extensive in this study.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The method of the structured descriptive assessment used in this study generally replicates that used and pioneered by Anderson and colleagues (Anderson & Long, 2002;Anderson et al, 2006;Freeman et al, 2000). However, this study differs from those listed in respect of the data analysis techniques used, which are more extensive in this study.…”
Section: Introductionmentioning
confidence: 91%
“…The treatment utility of the structured descriptive assessment has been affirmed by studies that have tested the effectiveness of interventions derived from it (Anderson & Long, 2002;Anderson, English, & Hedrick, 2006;Dolezal & Kurtz, 2010). Also, its external validity has been supported by its application with a typically developing population, and the subsequent implementation of effective interventions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These general procedures have been shown to be effective for evaluating the causes of challenging behavior (Anderson & Long, 2002; Freeman, Anderson, & Scotti, 2000). In addition, some recent research has suggested that these procedures are useful in typically developing populations (Anderson, English, & Hedrick, 2006).…”
Section: Functional Assessment and Intervention: Areas In Need Of Res...mentioning
confidence: 99%
“…Although the analog functional analysis is useful for identifying causal relations among environmental events, the extent to which the results of the analog enhance treatment utility is not certain. A growing body of research suggests that including idiosyncratic variables, such as caregivers, may result in different patterns of responding (English & Anderson;Ringdahl & Sellers, 2000;Sasso et al, 1992). It has not yet been determined if inclusion of caregivers or other idiosyncratic variables in the analog enhances the treatment utility of the assessment.…”
Section: Statement Of the Problemmentioning
confidence: 99%